2002
DOI: 10.1615/jwomenminorscieneng.v8.i1.30
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Achievement-Related Beliefs Among Engineering Students

Abstract: Achievement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 40 publications
2
49
3
Order By: Relevance
“…Namely, men and women tend to differ in their conceptions of ability. Female engineering students show greater tendency than their male counterparts to endorse the belief that engineering aptitude is a fixed entity as opposed to something that develops over time (Heyman et al 2002). Felder et al (1995) found that women were more likely than the men to attribute poor performance in engineering curriculum to their own lack of ability, while men were more likely to attribute it to a lack of hard work or being treated unfairly.…”
Section: Psychological Factors Values and Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, men and women tend to differ in their conceptions of ability. Female engineering students show greater tendency than their male counterparts to endorse the belief that engineering aptitude is a fixed entity as opposed to something that develops over time (Heyman et al 2002). Felder et al (1995) found that women were more likely than the men to attribute poor performance in engineering curriculum to their own lack of ability, while men were more likely to attribute it to a lack of hard work or being treated unfairly.…”
Section: Psychological Factors Values and Preferencesmentioning
confidence: 99%
“…Women may also perceive a hostile environment or differential treatment in prospective engineering programs. In general, female engineering students report greater discrimination than males-that they do not feel respected as equals, and that they more frequently experience discouraging interactions with faculty (Haines et al 2001;Heyman et al 2002;Shehab et al 2007;Suresh 2007;Vogt et al 2007).…”
Section: Perceptions Of the Fieldmentioning
confidence: 99%
“…Reports of overt racism and sexism from professors or peers still surface, particularly from students in the physical sciences and engineering (see, for instance, Heyman, Martyna, & Bhatia, 2002). More insidious, however, is the evidence that factors associated with success in college science differ by race, ethnicity, and gender (Ferreira, 2002;Heyman et al, 2002;Huang, Taddese, & Walter, 2000;Leslie, McClure, & Oaxaca, 1998;Lips, 1995;Sax, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…More insidious, however, is the evidence that factors associated with success in college science differ by race, ethnicity, and gender (Ferreira, 2002;Heyman et al, 2002;Huang, Taddese, & Walter, 2000;Leslie, McClure, & Oaxaca, 1998;Lips, 1995;Sax, 1994). Differences have been documented in motivation for studying science, patterns in taking science and mathematics courses, succeeding in college science, and persisting in or aspiring to science careers.…”
Section: Introductionmentioning
confidence: 99%
“…Simply put, students with better developed coping and academic control strategies and those with higher self-esteems have higher academic achievement than students who lack these dispositions (Brooks 1982;Crombie et al 2003;Heyman et al 2002;Jacobs 1996;Perry et al 2005;Sigmon et al 1995;Tamres et al 2002). This research also suggests that the psychosocial dispositions act as mediating pathways between the students' demographic characteristics (parental education, age, and gender, for example), academic programs (arts or sciences, for example), and their academic achievement in college.…”
Section: Psychosocial Variablesmentioning
confidence: 83%